Web-Based Expert System to Detect Stress on College Students - Grensya Bella Vega Persulessy; Nova S Pratama; Novianti Setiawan; Nina Sevani (ComTech: Computer, Mathematics and Engineering Applications, 2019)
This research aimed to make the application to detect stress for the college students. By early detecting stress on college students, it could help them to cope with their stress and avoid the negative impact of the stress. The Holmes-Rahe Readjustment Rating Scale was used to detect stress based on student’s life events. Each event had its score. There were 31 questions provided by the system. The final score would conclude the stress categories. Using the Forward Chaining Inference Engine, the system would collect the fact of the student’s life and give the result by accumulating scores on questions posed to the users from every question. The system also provided the reminder feature that led to continuous monitoring of stress condition in the students. About 65 correspondents who were selected using random sampling were asked to fill out questionnaires regarding this system after they tried the application. With the continuous monitoring, the researchers find that this system gives a result that all users have decreased their score of stress levels. Moreover, the correspondents rate that the design of the application is good enough, and the system is interesting and useful for helping students to provide a solution for stress.